From The Public and Private Rights of The Patient in Sharia Compared to The Law of The Parliament of The Kurdistan Region - Jarges Muhyiddin Muhammad Amin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research came about the patient’s right to Islamic Sharia compared to the law of the Kurdistan Region Parliament Iraq, and this research consists of three sections, in which I spoke about the definition of disease, the patient, medication, and the related words, then I mentioned the rule of medication and its consequences without detailing the provisions of the verses, and what is related to the rights of the patient from the point of view of general and specific to two cases of his general right, as well as two cases It is his private right, and I chose this research due to the patients' lack of knowledge of their rights and duties.He contributed to explaining something of that, and the greatness of Sharia, its humanity, and its concern for people's rights.